Connecting urban green spaces: the importance of irregular settlements in biodiversity and peri-urban planning - Risty Khoirunisa; Eka Permanasari; Muhamad Risqi U. Saputra; Maria H. Hällfors; Michaela F. Prescott; Alex M. Lechner (Urban Ecosystems, 2026)

Stropharia misionensis and S. viridis, two new species from native forests of Northern Argentina (Agaricomycetes, Agaricales) - Agustín P. Martínez; Juan M. Suárez; Joaquín Aliaga; Bernardo E. Lechner (Mycological Progress, 2026)

Enhancing urban forest connectivity: a multispecies modelling approach in Helsinki - Julia Hämäläinen; Alex M. Lechner; Johan Ekroos; Jiawei Zhao; Susanna Lehvävirta (Urban Ecosystems, 2026)
Understanding how landscape elements contribute to functional connectivity in a multispecies context is important to inform city planning. We compared the connectivity of urban forest habitats for three vertebrate species with contrasting dispersal modes: the Siberian flying squirrel ( Pteromys volans ), the common lizard ( Zootoca vivipara ) and European crested tit ( Lophophanes cristatus ). We used Graphab and Circuitscape, combined with literature- and expert opinion-based parameters to model their dispersal potential. We compared these models with designated existing connections and rerun the models with modelled future connections by the city of Helsinki, Finland. Our results suggest that despite the relatively high share of forests in Helsinki as compared to many capital cities in Europe and beyond, lack of connectivity may disrupt the movement in different ways for all three species. Isolation was mainly a result of either lack of habitat or too scarce connectivity elements combined with high landscape resistance. Isolation varied depending on species’ specific habitat requirements, interpatch-crossing distance and gap-crossing distance. Based on our models of functional connectivity, the designated existing connections were excessively optimistic. The modelled future connections enhanced connectivity, especially if created with sufficient quality for each species, yet only a small fraction of the modelled future connections was realistically convertible as pathways. Nevertheless, our approach can inform city planning by identifying critical connections and places, where strengthening or building functional connectivity would be beneficial. We suggest that city’s green wedges should be converted into a webbed urban green space network.

Human endothelial colony forming cells (ECFCs) require endothelial protein C receptor (EPCR) for cell cycle progression and angiogenic activity - Sarah E. J. Chambers; Jasenka Guduric-Fuchs; Edoardo Pedrini; Pietro M. Bertelli; Chutima Charoensuk; Elisa Peixoto; Varun Pathak; Hamza I. Alhamdan; Ruoxiao Xie; Anna Krasnodembskaya; Judith Lechner; Alan W. Stitt; et al. (Angiogenesis, 2025)
Vascular repair and regeneration are critical for tissue homeostasis. Endothelial colony forming cells (ECFCs) are vessel-resident progenitors with vasoreparative capacity and they offer an important avenue for allogeneic cytotherapy to achieve perfusion of ischemic tissues. Endothelial Protein C Receptor (EPCR) has been proposed as a marker for vascular endothelial stem cells, but its precise role in ECFC biology remains unknown. The current study has investigated the biological relevance of EPCR in ECFC function. Our data show that over 95% of ECFCs exhibit high EPCR expression. These levels surpassing CD34 and CD157, positions EPCR as a new robust ECFC immunophenotypic marker, alongside established markers CD31 and CD105. Functionally, depleting EPCR expression in ECFCs significantly diminished angiogenic activity, including proliferation, migration and tube formation. This knockdown also altered normal ECFC barrier function. Transcriptomic analysis indicated that knockdown of EPCR led to enrichment of gene signatures for cell cycle, TGF beta, and focal adhesion kinases. G1 cell cycle arrest was confirmed in ECFCs with depleted EPCR. Mechanistically, EPCR knockdown led to increased release of TGFβ2 and SMAD2/3 activation, coupled with increased p21, decreased pFAK, and increased transgelin. Additionally, we showed that quiescent ECFCs showed significantly lower EPCR expression when compared to proliferating ECFCs. In agreement with this, cell sorting experiments demonstrated that ECFCs with the highest EPCR expression exhibited the highest clonogenic capacity. In summary, our findings highlight that EPCR expression in ECFCs is critical for their angiogenic activity, by modulating cell cycle progression. Graphical abstract

Balancing landscape values and tourism choices: Integrating participatory mapping and the IPBES Values Typology - Liliana Solé; Kyle P. Hearn; Tahjudil Witra; Alex M. Lechner; Nora Fagerholm (Ambio, 2025)
The United Nations Educational, Scientific and Cultural Organization (UNESCO) Biosphere Reserves aim to balance nature and human coexistence, but increasing tourism challenges landscape management. The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) stresses the importance of understanding stakeholder values for effective management of natural spaces through a typology of intrinsic, instrumental, and relational values. This study applies this IPBES typology to tourism preferences in the Archipelago Sea Biosphere Reserve (ABR) using Public Participation Geographic Information Systems (PPGIS). A 2022 survey gathered data from 690 locals, recreationists, and tourists revealing intrinsic values as the most significant. Locals prioritized intrinsic and relational values, while recreationists and tourists emphasized relational and instrumental values. The study highlights a preference for small-scale tourism that preserves landscapes and heritage, illustrating the complexity of aligning stakeholder values in tourism and conservation. Insights from this research guide policymaking to better accommodate diverse values in protected areas.

Multi-modal deep learning approaches to semantic segmentation of mining footprints with multispectral satellite imagery - Muhamad Risqi U. Saputra; Irfan Dwiki Bhaswara; Bahrul Ilmi Nasution; Michelle Ang Li Ern; Nur Laily Romadhotul Husna; Tahjudil Witra; Vicky Feliren; John R. Owen; Deanna Kemp; Alex M. Lechner (Remote Sensing of Environment, 2025)

Stratospheric polar vortex, wave absorption/reflection and effect on surface climate - A. Hannachi; M. Lechner; K. Finke; D. Mukhin (Climate Dynamics, 2025)
The study of the stratosphere-troposphere interaction is important as it can contribute to boosting predictability in the subseasonal-to-seasonal timescale, particularly regarding extremes. This manuscript investigates the relationship between the stratospheric polar vortex and its sudden stratospheric warming and the troposphere in regard to the reflective and absorptive states of the vortex. We explore the eddy heat flux in relation to vertical wave propagation and sudden stratospheric warming, in addition to using the reflective index for comparison and checking. To find reflective and absorptive vortex regime and associated tropospheric flow, the analysis is complemented by clustering analysis. Using northern winter stratospheric and mid-tropospheric Reanalysis heights as well as sea level pressure and 2 m-temperature, absorptive and reflective states are identified and their coherent structures investigated in relation to the vortex state and surface climate. While the reflective index is not consistent with the eddy heat flux on the classification, the absorptive type for both methods consistently trigger a response in the annular mode with a negative Arctic Oscillation imprint. It also exhibits longer lasting wave propagation, compared to reflective types, suggesting sustained disruption of the circulation and occurrence of blocking. The clustering analysis reveals specific characteristics within vortex states affecting wave propagation. Precisely, weak and displaced or split vortex over the eastern hemisphere is associated with absorptive type, and yields more persistence, compared to the reflective type, associated with strong or quite weak vortex and also displaced vortex over North America. Effect on the surface climate are also discussed.

New species from Argentinean Yungas, Cercopemyces messii and Clitocybe cedrelae (Agaricomycetes, Agaricales) - Agustín P. Martínez; Juan M. Suárez; Joaquín Aliaga; Timothy J. Baroni; Bernardo E. Lechner (Mycological Progress, 2024)

First records of diurnal and nocturnal predatory birds from artificial hunting perch trials in oil palm plantations - Kamil Tohiran; Dzulhelmi Muhammad Nasir; Maisarah Burhanuddin; Frisco Nobilly; Raja Zulkifli; Ramle Moslim; Muhammad Syafiq Yahya; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (BioControl, 2024)

Corrigendum to “Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data” [Urban For. Urban Green. 98 (2024) 128415] - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

Thermal stressors during embryo incubation have limited ontogenic carryover effects in brook trout - Emily R. Lechner; Erin M.C. Stewart; Vince R. Frasca; Ken M. Jeffries; Chris C. Wilson; Graham D. Raby (Journal of Thermal Biology, 2024)

CT max in brook trout ( Salvelinus fontinalis ) embryos shows an acclimation response to developmental temperatures but is more variable than in later life stages - Emily R. Lechner; Erin M. C. Stewart; Chris C. Wilson; Graham D. Raby (Journal of Fish Biology, 2024)
Critical thermal maximum (CT max ) is widely used to measure upper thermal tolerance in fish but is rarely examined in embryos. Upper thermal limits generally depend on an individual's thermal history, which molds plasticity. We examined how thermal acclimation affects thermal tolerance of brook trout ( Salvelinus fontinalis ) embryos using a novel method to assess CT max in embryos incubated under three thermal regimes. Warm acclimation was associated with an increase in embryonic upper thermal tolerance. However, CT max variability was markedly higher than is typical for juvenile or adult salmonids.

Mapping development preferences on the perceived value of ecosystem services and land use conflict and compatibility in Greater Kuala Lumpur - Karen T. Lourdes; Chris N. Gibbins; Ben C. Sherrouse; Darius J. Semmens; Perrine Hamel; Ruzana Sanusi; Badrul Azhar; Jay Diffendorfer; Alex M. Lechner (Urban Forestry & Urban Greening, 2024)

Increasing mine waste will induce land cover change that results in ecological degradation and human displacement - John R. Owen; Deanna Kemp; Alex M. Lechner; Michelle Ang Li Ern; Éléonore Lèbre; Gavin M. Mudd; Mark G. Macklin; Muhamad Risqi U. Saputra; Tahjudil Witra; Anthony Bebbington (Journal of Environmental Management, 2024)

Differences in embryo survivorship among populations of brook trout (Salvelinus fontinalis) under variable winter thermal regimes - Erin M. C. Stewart; Emily R. Lechner; Vince R. Frasca; Chris C. Wilson; Graham D. Raby (Environmental Biology of Fishes, 2024)

Mapping public support for urban green infrastructure policies across the biodiversity-climate-society -nexus - Jussi Lampinen; Oriol García-Antúnez; Alex M. Lechner; Anton Stahl Olafsson; Natalie M. Gulsrud; Christopher M. Raymond (Landscape and Urban Planning, 2023)

Weight-gain independent effect of mirtazapine on fasting plasma lipids in healthy men - Katharina Lechner; Sarah Heel; Manfred Uhr; Tatjana Dose; Florian Holsboer; Susanne Lucae; Ludwig Schaaf; Stephany Fulda; Stefan Kloiber; Johannes M. Hennings (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Treatment with mirtazapine, a widely prescribed antidepressant, has been linked to weight gain and dyslipidemia. Whether dyslipidemia occurs secondary to increased appetite due to antidepressant treatment, or due to direct pharmacological effects of mirtazapine is unknown. The aim of this analysis is to complement our previously published results of the effect of mirtazapine on metabolism and energy substrate partitioning from a proof-of-concept, open-label clinical study (ClinicalTrials.gov NCT00878540) in 12 healthy males (20–25 years). We report the effect of a seven-day administration of mirtazapine 30 mg per day on weight and lipid metabolism in healthy men under highly standardized conditions with respect to diet, physical activity and day-night-rhythm and under continuous clinical observation. After a 7-day administration of mirtazapine 30 mg, we observed a statistically significant increase in triglyceride levels (mean change + 4.4 mg/dl; 95% CI [– 11.4; 2.6]; p = 0.044) as well as TG/HDL-C ratio (mean change + 0.2; 95% CI [– 0.4; 0.1]; p = 0.019) and a decrease in HDL-cholesterol (mean change – 4.3 mg/dl; 95% CI [2.1; 6.5]; p = 0.004), LDL-cholesterol (mean change – 8.7 mg/dl; 95% CI [3.8; 13.5]; p = 0.008), total cholesterol (mean change – 12.3 mg/dl; 95% CI [5.4; 19.1]; p = 0.005), and non-HDL-C (mean change – 8.0 mg/dl; 95% CI [1.9; 14.0]; p = 0.023). Notably, weight (mean change – 0.6 kg; 95% CI [0.4; 0.8]; p = 0.002) and BMI (mean change – 0.2; 95% CI [0.1; 0.2]; p = 0.002) significantly decreased. No change in waist circumference (mean change – 0.4 cm; 95% CI [– 2.1; 2.9]; p = 0.838) or waist-to-hip-ratio (mean change 0.0; 95% CI [– 0.0; 0.0]; p = 0.814) was observed. This is the first study showing unfavorable changes in lipid metabolism under mirtazapine in healthy individuals despite highly standardized conditions including dietary restriction, and despite the observation of a decrease of weight. Our findings support the hypothesis that mirtazapine has direct pharmacological effects on lipid metabolism. ClinicalTrials.gov: NCT00878540.

Identifying indicator bird species for sustainable oil palm plantation certification - Zulkifli Nursyamin; Muhammad Syafiq Yahya; Sharifah Nur Atikah; Kamil Azmi Tohiran; Ahmad R. Norhisham; Nurul Wahida Othman; Alex M. Lechner; Badrul Azhar (Journal of Cleaner Production, 2023)

Global assessment of the biodiversity safeguards of development banks that finance infrastructure - Divya Narain; Laura J. Sonter; Alex Mark Lechner; James E. M. Watson; Jeremy S. Simmonds; Martine Maron (Conservation Biology, 2023)
Infrastructure development is a major driver of biodiversity loss globally. With upward of US$2.5 trillion in annual investments in infrastructure, the financial sector indirectly drives this biodiversity loss. At the same time, biodiversity safeguards (project‐level biodiversity impact mitigation requirements) of infrastructure financiers can help limit this damage. The coverage and harmonization of biodiversity safeguards are important factors in their effectiveness and therefore warrant scrutiny. It is equally important to examine the extent to which these safeguards align with best‐practice principles for biodiversity impact mitigation outlined in international policies, such as that of the International Union for Conservation of Nature. We assessed the biodiversity safeguards of public development banks and development finance institutions for coverage, harmonization, and alignment with best practice. We used Institute of New Structural Economics and Agence Française de Développement's global database to identify development banks that invest in high‐biodiversity‐footprint infrastructure and have over US$500 million in assets. Of the 155 banks, 42% ( n = 65) had biodiversity safeguards. Of the existing safeguards, 86% (56 of 65) were harmonized with International Finance Corporation (IFC) Performance Standard 6 (PS6). The IFC PS6 (and by extension the 56 safeguard policies harmonized with it) had high alignment with international best practice in biodiversity impact mitigation, whereas the remaining 8 exhibited partial alignment, incorporating few principles that clarify the conditions for effective biodiversity offsetting. Given their dual role in setting benchmarks and leveraging private finance, infrastructure financiers in development finance need to adopt best‐practice biodiversity safeguards if the tide of global biodiversity loss is to be stemmed. The IFC PS6, if strengthened, can act as a useful template for other financier safeguards. The high degree of harmonization among safeguards is promising, pointing to a potential for diffusion of practices.

Reforestation could bring native mammal species back in the tropical highlands - Siti Wahdaniyah; Ku Noor Khalidah; Nabilah Hamidah Sabar; Norizah Kamarudin; Ruzana Sanusi; Norhisham Ahmad Razi; Alex M. Lechner; Badrul Azhar (Tropical Ecology, 2023)

Smallholder oil palm plantation sustainability assessment using multi-criteria analysis and unmanned aerial vehicles - Yong Bin Wong; Chris Gibbins; Badrul Azhar; Su Shen Phan; Paul Scholefield; Reza Azmi; Alex M. Lechner (Environmental Monitoring and Assessment, 2023)
Oil palm agriculture has caused extensive land cover and land use changes that have adversely affected tropical landscapes and ecosystems. However, monitoring and assessment of oil palm plantation areas to support sustainable management is costly and labour-intensive. This study used an unmanned aerial vehicles (UAV) to map smallholder farms and applied multi-criteria analysis to data generated from orthomosaics, to provide a set of sustainability indicators for the farms. Images were acquired from a UAV, with structure from motion (SfM) photogrammetry then used to produce orthomosaics and digital elevation models of the farm areas. Some of the inherent problems using high spatial resolution imagery for land cover classification were overcome by using texture analysis and geographic object-based image analysis (OBIA). Six spatially explicit environmental metrics were developed using multi-criteria analysis and used to generate sustainability indicator layers from the UAV data. The SfM and OBIA approach provided an accurate, high-resolution (~5 cm) image-based reconstruction of smallholder farm landscapes, with an overall classification accuracy of 89%. The multi-criteria analysis highlighted areas with lower sustainability values, which should be considered targets for adoption of sustainable management practices. The results of this work suggest that UAVs are a cost-effective tool for sustainability assessments of oil palm plantations, but there remains the need to plan surveys and image processing workflows carefully. Future work can build on our proposed approach, including the use of additional and/or alternative indicators developed through consultation with the oil palm industry stakeholders, to support certification schemes such as the Roundtable on Sustainable Palm Oil (RSPO).

Potential of agroforestry orchards as a conservation set-aside initiative in industrial rubber tree and oil palm plantations for avian biodiversity - Muhammad Syafiq Yahya; Sharifah Nur Atikah; Izereen Mukri; Aslinda Oon; Ainil Hawa; Ruzana Sanusi; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (Biodiversity and Conservation, 2023)

Assessment of CO2 and O2 spatial variability in an indigenous aquaculture system for restoration impacts - Evan Lechner; Yoshimi M. Rii; Kathleen Ruttenberg; Keli‘iahonui Kotubetey; Christopher L. Sabine (Frontiers in Marine Science, 2022)
Spatial variability in carbon dioxide (CO 2 ) and oxygen (O 2 ) was assessed within an Indigenous Hawaiian fishpond undergoing active ecosystem restoration. The brackish, tidal fishpond is located within Kāne‘ohe Bay, Hawai‘i. Following a year of monthly discrete sampling, a significant shift in DIC and percent O 2 saturation was observed along the North-South axis within the pond. The south end of the pond was higher in DIC (+35 μmol·kg⁻¹) and lower in percent O 2 saturation (-19%) than the north end, which exhibited values similar to those observed in water entering the fishpond from the bay. Water quality parameters and inequal proximity to water flux sites suggested that a difference in residence time may exist along the north-south axis. In addition, ΔTA/ΔDIC relationships revealed a respiration signal in south end of the pond, which was enhanced at depth. While physical processes strongly affect CO 2 and O 2 across various temporal scales, spatial patterns in biological processes may also affect variability within the fishpond. These findings demonstrate that changes in water chemistry within the fishpond are the result of ecosystem restoration efforts. In turn, future management decisions at the fishpond will play an important role in preserving its viability as a healthy habitat for the intended marine species.

Large‐scale reforestation can increase water yield and reduce drought risk for water‐insecure regions in the Asia‐Pacific - Hoong Chen Teo; Srivatsan V. Raghavan; Xiaogang He; Zhenzhong Zeng; Yanyan Cheng; Xiangzhong Luo; Alex M. Lechner; Matthew J. Ashfold; Aakash Lamba; Rachakonda Sreekar; Qiming Zheng; Anping Chen; et al. (Global Change Biology, 2022)
Large‐scale reforestation can potentially bring both benefits and risks to the water cycle, which needs to be better quantified under future climates to inform reforestation decisions. We identified 477 water‐insecure basins worldwide accounting for 44.6% (380.2 Mha) of the global reforestation potential. As many of these basins are in the Asia‐Pacific, we used regional coupled land‐climate modeling for the period 2041–2070 to reveal that reforestation increases evapotranspiration and precipitation for most water‐insecure regions over the Asia‐Pacific. This resulted in a statistically significant increase in water yield ( p

Evaluating the experimental cultivation of edible mushroom, Volvariella volvacea underneath tree canopy in tropical agroforestry systems - Nurul Kamaliah; Sabiha Salim; Sumaiyah Abdullah; Frisco Nobilly; Sapari Mat; Ahmad R. Norhisham; Kamil Azmi Tohiran; Raja Zulkifli; Alex M. Lechner; Badrul Azhar (Agroforestry Systems, 2022)

Landscape-scale Remote Sensing and Classification of Lentic Habitats in a Tropical City - Hoong Chen Teo; Matthew J. Hill; Alex M. Lechner; Fang Yenn Teo; Christopher N. Gibbins (Wetlands, 2021)

Measuring fire severity using UAV imagery in semi-arid central Queensland, Australia - Phill McKenna; Peter D. Erskine; Alex M. Lechner; Stuart Phinn (International Journal of Remote Sensing, 2017)

Effects of alcohol-induced working memory decline on alcohol consumption and adverse consequences of use - William V. Lechner; Anne M. Day; Jane Metrik; Adam M. Leventhal; Christopher W. Kahler (Psychopharmacology, 2016)

Characterizing Spatial Uncertainty when Integrating Social Data in Conservation Planning - A. M. Lechner; C. M. Raymond; V. M. Adams; M. Polyakov; A. Gordon; J. R. Rhodes; M. Mills; A. Stein; C. D. Ives; E. C. Lefroy (Conservation Biology, 2014)
Recent conservation planning studies have presented approaches for integrating spatially referenced social (SRS) data with a view to improving the feasibility of conservation action. We reviewed the growing conservation literature on SRS data, focusing on elicited or stated preferences derived through social survey methods such as choice experiments and public participation geographic information systems. Elicited SRS data includes the spatial distribution of willingness to sell, willingness to pay, willingness to act, and assessments of social and cultural values. We developed a typology for assessing elicited SRS data uncertainty which describes how social survey uncertainty propagates when projected spatially and the importance of accounting for spatial uncertainty such as scale effects and data quality. These uncertainties will propagate when elicited SRS data is integrated with biophysical data for conservation planning and may have important consequences for assessing the feasibility of conservation actions. To explore this issue further, we conducted a systematic review of the elicited SRS data literature. We found that social survey uncertainty was commonly tested for, but that these uncertainties were ignored when projected spatially. Based on these results we developed a framework which will help researchers and practitioners estimate social survey uncertainty and use these quantitative estimates to systematically address uncertainty within an analysis. This is important when using SRS data in conservation applications because decisions need to be made irrespective of data quality and well characterized uncertainty can be incorporated into decision theoretic approaches.

Numerical Simulations of Mould Electromagnetic Stirring for Round Bloom Strands - M. Barna; M. Javurek; J. Reiter; M. Lechner (BHM Berg- und Hüttenmännische Monatshefte, 2009)

The Sensitivity of Population Viability Analysis to Uncertainty about Habitat Requirements: Implications for the Management of the Endangered Southern Brown Bandicoot - DARREN M. SOUTHWELL; ALEX M. LECHNER; TERRY COATES; BRENDAN A. WINTLE (Conservation Biology, 2008)
Whenever population viability analysis (PVA) models are built to help guide decisions about the management of rare and threatened species, an important component of model building is the specification of a habitat model describing how a species is related to landscape or bioclimatic variables. Model‐selection uncertainty may arise because there is often a great deal of ambiguity about which habitat model structure best approximates the true underlying biological processes. The standard approach to incorporate habitat models into PVA is to assume the best habitat model is correct, ignoring habitat‐model uncertainty and alternative model structures that may lead to quantitatively different conclusions and management recommendations. Here we provide the first detailed examination of the influence of habitat‐model uncertainty on the ranking of management scenarios from a PVA model. We evaluated and ranked 6 management scenarios for the endangered southern brown bandicoot ( Isoodon obesulus ) with PVA models, each derived from plausible competing habitat models developed with logistic regression. The ranking of management scenarios was sensitive to the choice of the habitat model used in PVA predictions. Our results demonstrate the need to incorporate methods into PVA that better account for model uncertainty and highlight the sensitivity of PVA to decisions made during model building. We recommend that researchers search for and consider a range of habitat models when undertaking model‐based decision making and suggest that routine sensitivity analyses should be expanded to include an analysis of the impact of habitat‐model uncertainty and assumptions.

Optimierung von metallurgischen Prozessen mit Hilfe von Simulationen - M. Krobath; B. Kaufmann; M. Lechner; G. Ernst; K. Forstner; M. Javurek; S. Pirker (BHM Berg- und Hüttenmännische Monatshefte, 2008)

Absorption of short-chain fatty acids, sodium and water from the forestomach of camels - W. von Engelhardt; Ch. Dycker; M. Lechner-Doll (Journal of Comparative Physiology B, 2007)

Chewing activities and oesophageal motility during feed intake, rumination and eructation in camels - W. von Engelhardt; P. Haarmeyer; M. Kaske; M. Lechner-Doll (Journal of Comparative Physiology B, 2006)

The maximum attainable body size of herbivorous mammals: morphophysiological constraints on foregut, and adaptations of hindgut fermenters - M. Clauss; R. Frey; B. Kiefer; M. Lechner-Doll; W. Loehlein; C. Polster; G. E. Rssner; W. J. Streich (Oecologia, 2003)

Slowing of human arm movements during weightlessness: the role of vision - Mechtcheriakov S.; Berger M.; Molokanova E.; Holzmueller G.; Wirtenberger W.; Lechner-Steinleitner S.; C. De Col; Kozlovskaya I.; Gerstenbrand F. (European Journal of Applied Physiology, 2002)

The formation of empty shells upon pressure induced decapsidation of turnip yellow mosaic virus - M. Leimkühler; A. Goldbeck; M. D. Lechner; M. Adrian; B. Michels; J. Witz (Archives of Virology, 2001)

Degradation of 4-chloro-2-methylphenol by an activated sludge isolate and its taxonomic description - U. Lechner; R. Baumbach; D. Becker; V. Kitunen; G. Auling; M. Salkinoja-Salonen (Biodegradation, 1995)

Analysis of molecularly cloned DNA reveals minor differences among three virus strains of Aleutian disease of mink parvovirus - M. E. Bloom; D. Lechner; D. L. Wiedbrauk; J. B. Wolfinbarger (Archives of Virology, 1987)

The effect of carbaryl and malathion in combination on ?-glutamyl transpeptidase and glutathione S-alkyltransferase activityin vitro - D. Waidron Lechner; M. S. Abdel-Rahman (Archives of Environmental Contamination and Toxicology, 1986)

Combination effect of carbaryl and malathion in rats - Mohamed S. Abdel-Rahman; Doreen Waldron Lechner; Kenneth M. Klein (Archives of Environmental Contamination and Toxicology, 1985)